Urgensi Reformasi UU Narkotika dan UU ITE Menghadapi Ancaman Narkoba di Era Digital - Muhammad Natsir; Muh. Akbar Fhad Syahril; Ardiyanti Aris; A. Dzulqarnain (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2024)
This research examines the urgency of reform and harmonization Undang-Undang Narkotika (UU No. 35 Tahun 2009) dan Undang-Undang Informasi dan Transaksi Elektronik (UU No. 19 Tahun 2016) in facing the challenges of drug crime in the digital era. Through a normative juridical analysis of current cases and weaknesses in existing regulations, this study identifies an urgent need to expand the definition and scope of technology-based narcotics crimes, strengthen digital evidentiary aspects, regulate digital platform responsibilities, enhance international cooperation, integrate digital rehabilitation approaches, and provide special protection for children and adolescents in cyberspace. The study also emphasizes the importance of harmonization of the two laws accompanied by increasing the capacity of law enforcement in digital forensics and the use of advanced technologies such as artificial intelligence (AI) and big data analysis, while still paying attention to ethical aspects and human rights protection. The results of the study show that a comprehensive approach to legal reform is needed to create a more responsive and effective regulatory framework in tackling drug crime in the digital era, as well as anticipating technological developments and adaptations carried out by drug offenders in the future.